Non-Text Theses as an Integrated Part of the University Repository: a Case Study of the Academy of Performing Arts in Prague - Horová, Iva; Chvála, Radim (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2010)
Training the professional artists of the future brings several challenges. Students at the Academy of Performing Arts in Prague (AMU), at all degree levels, are required to produce outputs including several final qualifying works. A piece of written work is mandatory, but this is usually accompanied by records of artistic performance — a graduation film, a stage role, graphic materials, a concert, a set of photographs, etc. Each of these works has its own topic, tutor, opponents, annotations and even classifications. Some qualifying works, such as films, can have multiple student input, with different graduands in the roles of screenwriter, director, producer, and so on. The preservation and discovery of and access to these works are issues of obvious importance, just as is the case with ‘traditional’ textual works. These issues were addressed at AMU by modifications to an Open Source system, DSpace. Metadata based on the Dublin Core Standard was extended to include the relation element qualifiers. The modules for editing and displaying were modified to permit searching and viewing of the related documents. Video and audio players were integrated into the system to make the related multimedia files available directly from the primary record page. A handle server, which generates persistent identifiers, was implemented. The automatic transfer of metadata from the AMU Study information system, KOS, into the repository was enabled, along with automated OAI-PMH harvesting into the national registry Theses.cz at Masaryk University in Brno, and exports into the AMU library system. This paper is based on a presentation given by the lead author at the 2010 LIBER Annual General Conference, Aarhus, as part of the DART-Europe Master Class on the management of electronic theses.